Antibacterial properties of reactive oxygen species in carbon supported silica - DHANALAKSHMIVADIVEL; DANIELE DONDI; NITYA MEENAKSHIRAMAN; ILANCHELIANMALAICHAMY (International Journal of Pharma and Bio Sciences, 2018)
Radicals possess enhanced antibacterial activity due to their oxidation potential. This is well known since most inorganic disinfectants exploit this effect. Due to the instability of radicals, and following studies in the field, peroxyl radicals present at the interface of carbon-supported silicawere prepared from the pyrolysis of Kraft lignin onto high surface area silica (nanosilica).This material has stabilized peroxyl radicals that are formed by the reaction of the defective pyrolytic carbon with oxygen present in air. With this materialit is possible to vehiculate radical oxygen species (ROS) directly in the cells, due to the presence of nanosilica as a support. In the present study, the activity of these supported radicals has been tested against gram +ve and gram –ve bacteria. In particular, Bacillus subtilis and Klebsiella pneumonia were used as a test organism showing a zone of inhibition 09±1 and 19±2 respectively for a drug concentration of 120 ïM. The antibiograms obtained showed a good activity as antimicrobial agent, especially with K. pneumonia. The antibacterial activity was compared to that of doxorubicin.From the comparison, the material under this study has a comparable or superior activity when is used at the same concentration of doxorubicin. These encouraging results suggested us to move on the effect of the material in the eukaryotic cells.In fact, this could be interesting for anti-cancer treatment. The enhanced activity of peroxyl radicals at the interface of carbon supported silica over prokaryotic cells opening the avenue for the emerging research. The use of stabilized radicals could in fact be a second choice with respect the use of drugs. In fact, radical oxygen species are a specific and microorganism cannot develop resistance to radicals, as it happens in antibiotics.